2020
DOI: 10.1038/s41598-020-71316-z
|View full text |Cite
|
Sign up to set email alerts
|

An ossifying bridge – on the structural continuity between the Achilles tendon and the plantar fascia

Abstract: preconditioning cycles with a force range of 0.5 to 2.0 N were applied before the tissues were stretched until failure (Fig. 1C-E). All tissues were strained in the longitudinal axis according to the samples' predominant collagen orientation. The displacement rate was 20 mm/min and the sample reading rate was 100 Hz. A singlecharge coupled camera with a resolution of 2.8 Megapixels (Q400; Limess, Krefeld, Germany) and the ISTRA 4D software (VRS 4.4.1.354; Dantec Dynamics, Ulm, Germany) were used for strain dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…This thin fibrous band connects the plantar heel to the metatarsophalangeal joints [2]. PF is thought to be attached to the Achilles tendon via the superficial aligned trabeculae of the calcaneus, even if the continuity of collagen fibers between the Achilles tendon and the PF through the calcaneus is still debated [3]. PF has a fundamental biomechanical role in supporting the medial longitudinal arch of the foot [4][5][6] and is capable of storing strain energy and converting it into propulsive force, behaving as a quasi-elastic tissue [7], but it is in general characterized by relevant viscoelastic behavior [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This thin fibrous band connects the plantar heel to the metatarsophalangeal joints [2]. PF is thought to be attached to the Achilles tendon via the superficial aligned trabeculae of the calcaneus, even if the continuity of collagen fibers between the Achilles tendon and the PF through the calcaneus is still debated [3]. PF has a fundamental biomechanical role in supporting the medial longitudinal arch of the foot [4][5][6] and is capable of storing strain energy and converting it into propulsive force, behaving as a quasi-elastic tissue [7], but it is in general characterized by relevant viscoelastic behavior [8].…”
Section: Introductionmentioning
confidence: 99%
“…Few works in the literature have been carried out on the experimental testing of the mechanical properties of PF [3,8,22]; moreover, the possible effects of structural impairments on the mechanical behavior of fascia are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found a biomechanical link between the AT and PF by measuring the load-deformation properties in the PF under various conditions of the AT [5][6][7][8] . This biomechanical link provides grounds for hypothesizing that there is continuity between the AT and PF 9 . Indeed, some authors have described a lifelong continuity between the two structures [10][11][12] whilst others only agree of the continuity being in a fetal or neonatal population 13,14 , and others concluding that the connection ceases by late adulthood 15 .…”
mentioning
confidence: 95%
“…Future studies may add to these findings, examining tissues right after death without deep-freezing in comparison, thereby exploring the effects of deep-freezing on the here investigated biomechanical properties of the human TMF. Preconditioning of biological tissues for the aforementioned purposes is commonly done in tensile testing protocols as performed here 52 54 . However, the detailed effect of preconditioning on the biomechanical properties of biological tissues yet remains to be investigated in detail.…”
Section: Discussionmentioning
confidence: 99%